2020
DOI: 10.1186/s12969-020-0420-8
|View full text |Cite
|
Sign up to set email alerts
|

The elevated serum levels of calcineurin and nuclear factor of activated T-cells 1 in children with Kawasaki disease

Abstract: Background: The calcineurin and nuclear factor of activated T-cells (CaN-NFAT) signaling pathway had been found to be associated with Kawasaki disease (KD) susceptibility and coronary artery aneurysm formation as a contributor. To evaluate serum calcineurin (CaN) and nuclear factor of activated T-cells 1(NFAT1) levels in patients with Kawasaki disease (KD).Methods: Serum levels of CaN and NFAT1 were measured by enzyme-linked immunosorbent assay method in 66 healthy children and 74 KD patients at acute, afebril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recent observation confirmed the involvement of this pathway in KD, demonstrating that the serum levels of calcineurin and NFAT increased significantly in the acute stage and decreased progressively in the afebrile and subacute stage, reducing the CRP, white blood cell, and neutrophil counts [ 22 ]. Furthermore, an in vitro study using cultured endothelial cells of the coronary artery also suggested that the activation of the calcineurin/NFAT signaling pathway plays a vital role in causing the inflammation of the endothelial cells; Wang et al demonstrated that the serum of KD patients promoted the proliferation of coronary artery endothelial cells not only morphologically but also by increasing the expression of proteins involved in cell proliferation and proteins constituting the calcineurin/NFAT signaling pathway.…”
Section: Discussionmentioning
confidence: 85%
“…Recent observation confirmed the involvement of this pathway in KD, demonstrating that the serum levels of calcineurin and NFAT increased significantly in the acute stage and decreased progressively in the afebrile and subacute stage, reducing the CRP, white blood cell, and neutrophil counts [ 22 ]. Furthermore, an in vitro study using cultured endothelial cells of the coronary artery also suggested that the activation of the calcineurin/NFAT signaling pathway plays a vital role in causing the inflammation of the endothelial cells; Wang et al demonstrated that the serum of KD patients promoted the proliferation of coronary artery endothelial cells not only morphologically but also by increasing the expression of proteins involved in cell proliferation and proteins constituting the calcineurin/NFAT signaling pathway.…”
Section: Discussionmentioning
confidence: 85%
“…The CaN-NFAT signaling pathway plays a crucial role in promoting the expression of cytokines, such as IL-2 and IFN-γ, leading to the activation of T cells ( 32 ). Downregulation of CaN phosphorylation inhibits NFAT from entering the nucleus, inhibiting T cells activation.…”
Section: Discussionmentioning
confidence: 99%